Strength of soft clay reinforced with encapsulated bottom ASH columns - Wan Nursyafiqah, Wan Jusoh (2019)
The uncontrollable usage of non-renewable natural resources and production of waste gives severe impact on the earth. The uncontrollable usage of bottom ash (waste material) can cause pollution to the environment. The vert ical granular columns has the properties to improve the bearing capacity, reduce the settlement, and accelerate the dissipation of excess pore water pressure of the weak soil. The aim of this research is to investigate the role of single and group encapsulated bottom ash columns in improving the shear strength of the soft reconstituted kaolin clay by using the laboratory scale model. The shear strength characteristic can be obtained by determining the effect of area replacement ratio, height penetration rat io, and volume replacement ratio on single and group of encapsulated bottom ash columns. The reinforced kaolin samples were tested under Unconfined Compression Test (UCT) and Unconsolidated Undrained Triaxial Test (UU). The specimen used were 50 mm in diameter and 100 mm in height. Using the encapsulated bottom ash column reinforcement of 0.6, 0.8, and 1.0 height penetrating ratio with 10 and 16 mm diameters columns while the specimen without any reinforcement was referred as the controlled samples. The hig hest improvement of shear strength of the single encapsulated bottom ash column on area replacement ratio of 4.00 % at 10 mm diameter columns is at 0.8 height penetration ratio with 77.00% while for area replacement ratio of 10.24% at 16 mm diameter columns is also at 0.8 height penetration ratio with 71.48%. Meanwhile, the highest improvement of shear strength of the group encapsulated bottom ash column on area replacement ratio of 12.00 % at 10 mm diameter columns is at 0.8 height penetration ratio with 75.63% while for area replacement ratio of 30.72% at 16 mm diameter columns is also at 0.8 height penetration ratio with 56.41%. The maximum improvement of shear strength was at 0.8 height penetrating ratio for both single and group encapsulated bottom ash columns. UU testing showed the significant improvement on cohesion which was recorded to be from 4.31% to 89.21%, and the improvement of friction angle, φ was from 4.17% to 27.92%. The improvement of deviator stress versus axial strain at failure of 70 kPa, 140 kPa, and 280 kPa for cell pressure were recorded to be at between 12.55%–51.80%. In conclusion, the installation of single and group encapsulated bottom ash columns can improve the shear strength and the compressibility of the soft reconstituted kaol in clay.